Peran Teknologi Pascapanen Ubi Jalar dalam Menunjang Ketahanan Pangan Komunitas Perdesaan - Wardhan, Mia Agus (Jurnal Ilmu-Ilmu Pertanian, 2025)
This study aimed to analyze the role of post-harvest technology in supporting food security within rural communities, using a case study of sweet potato processing. Sweet potatoes were selected as the focus due to their status as a locally available, highly nutritious crop that is easy to cultivate but prone to post-harvest losses of up to 30–40% if not properly handled. The research employs a qualitative descriptive method through literature reviews and empirical document analysis from the practices of farmer groups and village-owned enterprises (BUMDes) in several regions of Indonesia. The data were analyzed based on three main aspects: the effectiveness of post-harvest technology in reducing yield loss, the contribution of value-added processing to the local economy, and the role of local institutions in promoting the adoption of such technologies. The findings indicate that curing—performed at 25–32 °C with high humidity for 4–10 days—significantly reduces tuber damage and extends storage life up to five months. Additionally, transforming sweet potatoes into value-added products such as chips and flour increases farmers’ household income by 25–35%. The successful implementation of these technologies is also strongly influenced by active local institutions that provide training, equipment, and market access. The study concludes that the integration of technological innovation and institutional support can effectively enhance food security and promote sustainable economic development in rural communities.